Drug Repurposing in the Treatment of Traumatic Brain Injury - Ghiam, Michael K.; Patel, Shrey D.; Hoffer, Alan; Selman, Warren R.; Hoffer, Barry J.; Hoffer, Michael E. (Frontiers in Neuroscience, 2021)
Traumatic brain injury (TBI) is the most common cause of morbidity among trauma patients; however, an effective pharmacological treatment has not yet been approved. Individuals with TBI are at greater risk of developing neurological illnesses such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The approval process for treatments can be accelerated by repurposing known drugs to treat the growing number of patients with TBI. This review focuses on the repurposing of N-acetyl cysteine (NAC), a drug currently approved to treat hepatotoxic overdose of acetaminophen. NAC also has antioxidant and anti-inflammatory properties that may be suitable for use in therapeutic treatments for TBI. Minocycline (MINO), a tetracycline antibiotic, has been shown to be effective in combination with NAC in preventing oligodendrocyte damage. (−)-phenserine (PHEN), an anti-acetylcholinesterase agent with additional non-cholinergic neuroprotective/neurotrophic properties initially developed to treat AD, has demonstrated efficacy in treating TBI. Recent literature indicates that NAC, MINO, and PHEN may serve as worthwhile repositioned therapeutics in treating TBI.